Impact of self-efficacy and mediating factors on Fintech adoption in the VUCA era - Thi Chinh, Nguyen; The Anh, Khuc; Nguyen Duc, Duong; Phuong Kim Quoc, Cuong; Linh, Le Dieu (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This paper aims to understand the impact of factors affecting the relationship between intention and using Fintech in the VUCA era, which stands for volatility, uncertainty, complexity, and ambiguity. A cross-sectional design was employed in this study. The data was collected via questionnaires, with 1,411 usable responses received through the survey. Partial least squares structural equation modeling (PLS-SEM) was employed to assess the process with SmartPLS 4. Our research did figure out the positive impact of Perceived Usefulness and Perceived Ease of use on behavioral intention and the positive impact of Intention on Using Fintech behavior. Simultaneously, we indicated that Financial literacy could moderate the relationship between Intention and Using Fintech behavior, and Financial self-efficacy would be a mediator of the association between Financial literacy and Using Fintech behavior. Based on the results, we make some recommendations for Fintech developers in Vietnam.